KEMANDIRIAN KOPERASI DAN ANALISIS EFISIENSI USAHA (STUDIKASUS PADA KUD TUWUH SARI DI DESA PURWODADI, KECAMATAN ANGSANA,KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN) - Syukur Abdurrozaq; Daru Retnowati; Heni Handri Utami (Jurnal Dinamika Sosial Ekonomi, 2018)
This research aims are (1) analyze the independence level of KUD Tuwuh sari, (2) analyze the efficiency of KUD Tuwuh Sari seen from its business turnover rate, (3) analyze the efficiency of KUD Tuwuh Sari from the rotation of working capital. The research method uses descriptive method. Method of implementation uses case study method. The data uses secondary data obtained from KUD Tuwuh Sari and complementary data (obtained from the institutions closely related to this research). Techniques Data collection uses interviews, recording, observation and documentation. This research shows that the Independence Rate KUD Tuwuh Sari was high level. For business efficiency of KUD Tuwuh Sari seen from the Business Capital Turnover Rate have been efficient, but for the efficiency of KUD Tuwuh Sari seen from the Capital Turnover Level has not been efficient. Keywords: Cooperative, Independence, Business Efficiency.